2021
DOI: 10.1186/s12905-021-01305-5
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity among women with stroke: health, demographic and healthcare utilization differentials

Abstract: Background Although age specific stroke rates are higher in men, women have a higher lifetime risk and are more likely to die from a stroke. Despite this increased severity, most studies focus on male/female differences in stroke onset, patterns of care and stroke-related outcomes. Given that stroke presents differently in men and women, mixed sex studies fail to fully capture heterogeneity among women with stroke and the subsequent impact on their outcomes. This study examined the sociodemogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In light of the increasing prevalence of this disorder in women of advanced age [ 25 ] and recent work implicating that hypertension is associated with greater stroke risk in women than in men [ 26 ], effective treatment and control of hypertension is an essential component for stroke prevention in elderly women. A recent study identified important differences between young and older women regarding risk and lifestyle factors associated with stroke incidence and post-stroke functional impairment, necessitating age-dependent differential approaches in secondary and tertiary stroke prevention [ 27 ]. With all other vascular risk factors more frequently found in men aged >70–≤90 years, it is not surprising that strokes caused by large and small vessel disease show a distinct male predominance.…”
Section: Discussionmentioning
confidence: 99%
“…In light of the increasing prevalence of this disorder in women of advanced age [ 25 ] and recent work implicating that hypertension is associated with greater stroke risk in women than in men [ 26 ], effective treatment and control of hypertension is an essential component for stroke prevention in elderly women. A recent study identified important differences between young and older women regarding risk and lifestyle factors associated with stroke incidence and post-stroke functional impairment, necessitating age-dependent differential approaches in secondary and tertiary stroke prevention [ 27 ]. With all other vascular risk factors more frequently found in men aged >70–≤90 years, it is not surprising that strokes caused by large and small vessel disease show a distinct male predominance.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of strokes is higher, and the outcomes are worse among women. This is due to women typically living longer and stroke risk increasing with age [ 28 , 29 , 30 ]. In addition, women present with more severe neurologic impairments following a stroke and are less likely to receive acute stroke therapies and have worse functional outcomes after hospitalizations [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to findings of an existing South African study that highlighted a higher prevalence of strokes among females (Ferris & Naicker 2020 ). Despite age-specific stroke rates being higher in males, females are more at risk of having more stroke events that they are less likely to recover from because of their longer life expectancy (Girijala et al 2017 ; Jacobs & Ellis 2021 ; Reeves et al 2008 ). These current findings are also comparable to a study conducted at CHBAH, which found ischaemic strokes more prevalent in women than men (Mudzi et al 2012 ).…”
Section: Discussionmentioning
confidence: 99%